POSHAN's abstract digest on maternal and child nutrition research - Issue 26 - Avula, Rasmi (International Food Policy Research Institute, 2019)
We are delighted to present to you the first issue of Abstract Digest for this year. This issue has two important LANCET Commission Reports. The EAT–Lancet Commission is the first of a series of initiatives on nutrition, led by The Lancet in 2019, followed by the Commission on the Global Syndemic of obesity, undernutrition, and climate change. Along with these, we have articles from an issue of Public Health Nutrition that focuses on child and adolescent nutrition, and much more.